P046 Necrostatin-1 ameliorates neutrophilic asthma by inhibiting neutrophil release nets. (March 2019) - Han, X; Jie, H; Wang, J; Zhang, J; He, J; Yu, C; Sun, E
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Neutrophilic asthma is Corticosteroid-resistant and increases the burden of global health care. Multiple studies have indicated that there are a large amount of neutrophil extracellular traps (NETs) in the airways of neutrophil asthmatics. 1 Although NETs are able to entrap and kill pathogens, extensive accumulation of NETs which aggravate the condition of asthmatics and promote the progression of the disease. 2 However to our knowledge, the mechanisms by which NETs influence the progression of asthma have not been clearly elucidated and neutrophilic asthma requires novel effective therapeutic strategies. Objectives: We sought to explore the underlying mechanisms of NETs aggravate the severity of asthma, and to investigate a new strategy of effective treatment against corticosteroid-insensitive neutrophilic asthma. Methods: Mouse models of neutrophil-dominated asthma and phorbolester(PMA) aggravated neutrophil asthma were used in this study to clarify the role of NETs in the pathogenesis of neutrophil asthma. Neutrophil release NETs was detected in bronchoalveolar lavage fluid (BALF)of neutrophil-dominated asthma. Finally a small molecule Necrostatin-1(Nec-1) which has been shown to inhibit neutrophil release NETs was tested for its therapeutic effects against neutrophilic airway inflammation. Results: NETs could induce human epithelium human bronchial epithelial cell deth and detachment in vitro study. NETs significantly increased in neutrophil asthma model and PMA aggravated neutrophil asthma. In vivo studies, Nec-1 could relieve airway hyperresponse, also reduced total protein, myeloperoxidase activity and inflammatory cytokines. Histological examination of the lungs also showed that Nec-1 markedly reduced the inflammation. We further explored that Nec-1 could induce human neutrohils and mice BALF neutrohils apoptosis. BALF and lung tissue immunofluorescence showed neutrophils increased expression of cleaved-casepase. 3 Conclusions: NETs could damage airway epithelium and trigger inflammatory responses. Nec-1 inhibit neutrophil release NETs ameliorates neutrophil airway inflammation. May be the inherent mechanism of Nec-1 inhibit neutrophil release NETs is related to it specificitly promotes neutrophil apoptosis. References: Porto BN, et al . Neutrophil Extracellular Traps in Pulmonary Diseases: Too Much of a Good Thing? Frontiers Immunolugy 2016;7:311. Toussaint M, et al . Host DNA released by NETosis promotes rhinovirus-induced type-2 allergic asthma exacerbation. Nature Medicine, 2017;23(6):681–691. Pham, DL, et al. Neutrophil autophagy and extracellular DNA traps contribute to airway inflammation in severe asthma. Clin Exp Allergy, 2017;47(1):57–70. Acknowledgements: Thanks to the colleagues in the team of Dr Erwei Sun. Disclosure of Interest: None declared.